Almost zero-fluoroscopy LBBP-procedure using a 3D-mapping system. (3rd October 2022) - Derndorfer, M; Puererfellner, H; Martinek, M R; Kollias, G
Abstract: Introduction: Cardiac device therapy has recently been extended by the option of Conduction System Pacing, CSP (HIS Bundle Pacing, HBP; Left Bundle Branch Area Pacing, LBBAP). Similar to cardiac resynchronization therapy (CRT), complex procedures can result in long fluoroscopy-duration and considerable radiation exposure for the patient and the implanting team. According to the principle ALARA (As Low As Reasonably Achievable), measures should be taken to reduce radiation, wherever possible. We report the almost fluoroscopy-free implantation of a LBBAP-system using a 3D electroanatomical mapping system (EAMS). The patient was indicated for a pace & ablate concept due to recurrent, highly symptomatic, persistent atrial fibrillation (AF), a history of mitral valve repair and a severely dilated left atrium. ESC guidelines suggest choosing a RV-lead (indication IIa), alternatively either a CRT system or HBP (both IIb). LBBAP as new option for physiological pacing was chosen in this patient because it usually provides excellent stimulation thresholds and the lead – in contrast to HBP – is distant from Koch's triangle, so that AV-nodal-ablation can be performed safely. Methods: Surgery was performed under deep sedation. After accessing the cephalic vein, a quick 3D map of relevant structures was acquired (right atrium; coronary sinus; HIS; interventricular septum, IVS). Then a preformed sheath and a stylet-driven pacemaker-lead were advanced. The lead-tip was visualized within the EAMS and maneuvered without fluoroscopy. After approaching the proximal IVS, the implantation site was confirmed by unipolar stimulation and the lead was advanced into the IVS under close monitoring of impedance and signals. Final position was confirmed by sheath-angiography [Fig. 1]. Results: During lead fixation, LBBAP-typical ECG-changes (progression to rSR morphology, fixation beats) could be observed. A left bundle branch potential (poLBB) could be documented. The left ventricular activation time (LVAT) as a marker of rapid LV-excitation was shortened from 108 ms to 68 ms. Thresholds for non-selective and selective LBBP were 3 V @ 1 ms and 0.7 V @ 0.4 ms, with a sensing of 8.7 mV, impedance of 643 ohms and a paced QRS-width of 112 ms [Fig. 2]. An atrial lead was added (history of intermittent sinus rhythm) and a dual-chamber pacemaker was connected. Fluoroscopy was required for lead fixation into the IVS, atrial lead placement as well as for sheath angiography and lead length-optimization. Total fluoroscopy time was 1.13 minutes with a radiation dose of 45.04 μGy m 2, procedure time 64 minutes. AVN total ablation was performed the following day without complications. Conclusions: CSP using a 3D mapping system is simple, facilitates understanding of important anatomical structures and helps to reduce the required radiation dose to a necessary minimum. In individual cases, procedures requiring almost zero-fluoroscopy are possible. Funding Acknowledgement: Type of funding sources: None.